Cilostazol protects against microvascular brain injury in a rat model of type 2 diabetes. (April 2017) - Tsukamoto, Yuko; Nagata, Eiichiro; Fukuyama, Naoto; Itoh, Yoshiko; Yuzawa, Hiroko; Kohara, Saori; Shimizu, Mie; Takahari, Yoko; Takizawa, Shunya
Highlights: Cilostazol is useful for preventing recurrent brain vascular events. We investigated the effect of cilostazol on diabetic brain vasculopathy in rats. Cilostazol could improve autoregulatory responses in cortical cerebral arteries. Abstract: Cilostazol, a pluripotent phosphodiesterase III-specific inhibitor with anti-platelet and vasculogenic effects, is useful for preventing recurrent brain vascular events, particularly in stroke patients with diabetes mellitus (DM). However, it is unclear whether cilostazol affects autoregulatory responses in small cerebral arteries. Thus, we investigated the effect of cilostazol on diabetic brain vasculopathy in a model of type II DM using male OLETF rats. OLETF rats were treated with either cilostazol (CG) or vehicle (VG) and subjected to microangiography with monochromatic synchrotron radiation to investigate middle cerebral artery (MCA) vasoreactivity following an injection of acetylcholine (Ach). Ach administration led to MCA diameter contraction in the VG, but MCA dilation in the CG. We also evaluated morphological changes in the small intracranial vessels and found that in the CG, the endothelial cell structure in the small artery was not destroyed. Moreover, protein levels of phosphorylated endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor (VEGF) were higher in each evaluated brain region in CG rats vs. VG rats. Our results suggest that cilostazol could potentially improve autoregulatory responses in the small cerebral arteries by increasing eNOS phosphorylation and VEGF expression in DM, and thus, may act as a neurovascular protectant.